2015
DOI: 10.5507/fot.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

Diatom assemblages of non-living substrates in petrifying Cratoneurion springs from lower Belgium

Abstract: Diatom assemblages were examined from non-living substrates in thirteen springs supporting the Natura 2000 habitat type 'Petryfing springs with tufa formation' in the southern part of Flanders. More than 300 taxa were recorded, including some which appear to be particularly associated with this kind of environment. Even though a number of characteristic taxa and diatoms characterizing fast-flowing springs of more elevated terrain remained absent, local species richness was higher than reported from carbonate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…The restricted range of pH suitable for its colonization, in- In the site (sample) codes the number is referred to the elevation of the spring, and the final "m" denotes a bryophyte ("moss") sample (more details in Table 1 Wojtal 2013). The assemblages of the springs studied also show analogies with those of petrifying springs affected by nitrate enrichment (denyS & ooSterlynck 2015), which is consistent with the fact that the springs studied included limestone precipitating springs. The most characteristic algae (species involved in biocalcification processes) of LPS appear to be less sensitive to nitrate than to phosphate enrichment (Cantonati et al 2016 Besides other anthropogenic pressures (nitrates, artificial morphology of the site of emergence), an important driver is the low discharge, that is likely to cause extensive parts of the substrata to dry out during low flow.…”
Section: Diatom Assemblage Composition and Main Environmental Determisupporting
confidence: 82%
See 1 more Smart Citation
“…The restricted range of pH suitable for its colonization, in- In the site (sample) codes the number is referred to the elevation of the spring, and the final "m" denotes a bryophyte ("moss") sample (more details in Table 1 Wojtal 2013). The assemblages of the springs studied also show analogies with those of petrifying springs affected by nitrate enrichment (denyS & ooSterlynck 2015), which is consistent with the fact that the springs studied included limestone precipitating springs. The most characteristic algae (species involved in biocalcification processes) of LPS appear to be less sensitive to nitrate than to phosphate enrichment (Cantonati et al 2016 Besides other anthropogenic pressures (nitrates, artificial morphology of the site of emergence), an important driver is the low discharge, that is likely to cause extensive parts of the substrata to dry out during low flow.…”
Section: Diatom Assemblage Composition and Main Environmental Determisupporting
confidence: 82%
“…In spite of being the sole widely-distributed spring type included in the European Union Habitat Directive (EU-HD 1992), LPS are affected by many impacts, the most important ones being water diversion, and inadequate management due to lack of appreciation. The charac-teristics of diatom assemblages of petrifying springs affected by nitrate enrichment were recently discussed by denyS & ooSterlynck (2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that NH 4 and PO 4 variables act in the same way ( Figure 2). More curiously though is the opposite relation between these two variables and the NO 3 concentration though a similar observation has been made by Denys and Oosterlynck [48] in Flanders. The second axis showed that the canopy cover also plays an important role in the dispersion of the species assemblages.…”
Section: Global Analysissupporting
confidence: 69%
“…The negative relation with PO 4 , and with NH 4 when keeping the outliers in the dataset, indicates that the more oligotrophic the conditions the more rich the community. Other studies indicate that this kind of relationship is not always attributed to eutrophication, and human impacts are sometimes positively correlated to species richness [48]. These studies may address a wider range of conditions than in the present study and suggest that this relationship is scaledependent.…”
Section: Species Richnessmentioning
confidence: 43%
“…Diatom valves are counted (~400 valves are required to adequately represent species assemblages) and identified on each slide along random transects with a Leica DMRX light microscope (Leica Microsystems GmbH, Wetzlar, Germany) (or any other microscope with similar performances and equipped with a 100× oil immersion objective) at a magnification of 1000× using the most updated taxonomic books and monographs (e.g., Refs ). The ecological classification is typically based on the Van Dam et al system using the software (OMNIDIA 6.0.2), refined and updated with the inclusion of information concerning poorly known aerial species (e.g., Refs ).…”
Section: Terrestrial Diatom Sampling and Identificationmentioning
confidence: 99%